Multiple steps of prion strain adaptation to a new host - Bocharova, Olga; Makarava, Natallia; Pandit, Narayan P.; Molesworth, Kara; Baskakov, Ilia V. (Frontiers in Neuroscience, 2024)
The transmission of prions across species is a critical aspect of their dissemination among mammalian hosts, including humans. This process often necessitates strain adaptation. In this study, we sought to investigate the mechanisms underlying prion adaptation while mitigating biases associated with the history of cross-species transmission of natural prion strains. To achieve this, we utilized the synthetic hamster prion strain S05. Propagation of S05 using mouse PrP C in Protein Misfolding Cyclic Amplification did not immediately overcome the species barrier. This finding underscores the involvement of factors beyond disparities in primary protein structures.Subsequently, we performed five serial passages to stabilize the incubation time to disease in mice.The levels of PrP Sc increased with each passage, reaching a maximum at the third passage, and declining thereafter. This suggests that only the initial stage of adaptation is primarily driven by an acceleration in PrP Sc replication. During the protracted adaptation to a new host, we observed significant alterations in the glycoform ratio and sialylation status of PrP Sc N-glycans. These changes support the notion that qualitative modifications in PrP Sc contribute to a more rapid disease progression. Furthermore, consistent with the decline in sialylation, a cue for "eat me" signaling, the newly adapted strain exhibited preferential colocalization with microglia. In contrast to PrP Sc dynamics, the intensity of microglia activation continued to increase after the third passage in the new host. In summary, our study elucidates that the adaptation of a prion strain to a new host is a multi-step process driven by several factors.